2020
DOI: 10.1002/anie.202010829
|View full text |Cite
|
Sign up to set email alerts
|

Colyliform Crystalline 2D Covalent Organic Frameworks (COFs) with Quasi‐3D Topologies for Rapid I2 Adsorption

Abstract: Constructing three‐dimensional (3D) structural characteristics on two‐dimensional (2D) covalent organic frameworks (COFs) is a good approach to effectively improve the permeability and mass transfer rate of the materials and realize the rapid adsorption for guest molecules, while avoiding the high cost and monomer scarcity in preparing 3D COFs. Herein, we report for the first time a series of colyliform crystalline 2D COFs with quasi‐three‐dimensional (Q‐3D) topologies, consisting of unique “stereoscopic” tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
137
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(149 citation statements)
references
References 47 publications
12
137
0
Order By: Relevance
“…FT‐IR (Figure S4) showed that the reaction between TAPT and the dialdehydes (DMTA/DHTA) had occurred, evidenced by the disappearance of bands at 3359–3428 cm −1 (amino groups) and 1668.2 cm −1 (aldehyde groups) and the appearance of the characteristic ‐C=N‐ stretching band at ≈1679 cm −1 . Moreover, the presence of the characteristic hydroxyl band at 3260 cm −1 in the FT‐IR spectrum of COF‐OH‐50 confirmed that DHTA entities had been incorporated in its framework [9b] . The characteristic signals of ammonium salt at 2898–3002 cm −1 were observed in the spectrum of iCOF‐AB‐50 (Figure S4), suggesting that ionic AB groups had been grafted onto the framework via post‐synthesis modification.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…FT‐IR (Figure S4) showed that the reaction between TAPT and the dialdehydes (DMTA/DHTA) had occurred, evidenced by the disappearance of bands at 3359–3428 cm −1 (amino groups) and 1668.2 cm −1 (aldehyde groups) and the appearance of the characteristic ‐C=N‐ stretching band at ≈1679 cm −1 . Moreover, the presence of the characteristic hydroxyl band at 3260 cm −1 in the FT‐IR spectrum of COF‐OH‐50 confirmed that DHTA entities had been incorporated in its framework [9b] . The characteristic signals of ammonium salt at 2898–3002 cm −1 were observed in the spectrum of iCOF‐AB‐50 (Figure S4), suggesting that ionic AB groups had been grafted onto the framework via post‐synthesis modification.…”
Section: Resultsmentioning
confidence: 73%
“…Besides equilibrium adsorption capacity, adsorption kinetics is also important for practical applications. Indeed, to achieve higher I 2 removal efficiency and adsorbent utilization efficiency, the adsorbent is usually replaced and regenerated before reaching 80 % of its full capacity [9b] . Thus, the average adsorption rate determined at 80 % of the full adsorption capacity (defined as K 80 % ) is used as an important indicator for evaluating adsorbent performance.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, inorganic adsorbents, 7,8 such as ion-exchange zeolites 9,12,13 and silver-functionalized silica aerogels, 10,11 usually exhibit high cost, low uptake capacities and instability toward water and moisture. In recent years, metal-organic frameworks (MOFs) [14][15][16][17][18][19][20] and porous organic polymers (POPs), [21][22][23][24][25] which include conjugated microporous polymers (CMPs), 25,26 covalent triazine frameworks (CTFs), 27 charged porous aromatic frameworks (PAFs) 21,28,29 and covalent organic frameworks (COFs), 24,[30][31][32][33][34][35][36][37][38][39][40][41] have attracted a lot of attention for worthwhile iodine capture. POPs have been found to exhibit high potential for iodine capture and storage due to their high surface area, and the high interaction between adsorbents and iodine.…”
Section: Introductionmentioning
confidence: 99%
“…The crystalline porous structure of COF has provided an excellent skeleton for hosting the iodine species. For example, some COFs 32,38 (TPB-DMTP COF, 6.2 g g À1 ; QTD-COF-V, 6.29 g g À1 ) have achieved more than 6 g g À1 iodine uptake. A fast and effective design or screen method of high iodine capture COFs is meaningful for radiological nuclear waste capture and storage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, COFs have shown potential for the removal and capture of other gas molecules, as methane and sulfur dioxide, among others [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. One of these promising materials, Meso-COF-3, synthesized from the triamine with terephthalaldehyde, was one of the largest COFs regarding available pore parameters (4 nm pore diameter, 0.84 cm 3 g –1 pore volume and a BET surface area of 986 m 2 g −1 ) and showed an outstanding iodine adsorption capacity of up to 4000 mg g −1 , at 75 °C [ 65 ].…”
Section: Cof Applicationsmentioning
confidence: 99%